Signaling Firm Performance Through Financial Statement Presentation: An Analysis Using Special Items - RIEDL, EDWARD J.; SRINIVASAN, SURAJ (Contemporary Accounting Research, 2010)
This paper investigates whether managers’ presentation of special items within the financial statements reflects economic performance or opportunism. Specifically, we assess special items presented as a separate line item on the income statement (income statement presentation) to those aggregated within another line item with disclosure only in the footnotes (footnote presentation). Our study is motivated by standard‐setting interest in performance reporting and financial statement presentation, as well as prior research investigating managers’ presentation choices in other contexts. Empirical results reveal that special items receiving income statement presentation are less persistent relative to those receiving footnote presentation. These results are consistent across numerous alternative specifications. Overall, the findings are consistent with managers using the income statement versus footnote presentation to assist users in identifying those special items most likely to differ from other components of earnings — that is, for informational, as opposed to opportunistic, motivations.